Penerapan Blockchain Untuk Keamanan Data Rekam Medis Elektronik : Literatur Review - Nicholas Alexander; Monalisa; Bayu Angga Wijaya; Rico Wijaya Dewantoro (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Blockchain is a modern technology with the capability to create a high level of transparency in data processing. Due to this capability, blockchain has begun to evolve across various sectors, one of which is the healthcare sector. This literature review examines the implementation of blockchain in healthcare systems, focusing on security management in electronic medical records (EMR) and clinical trial data management. A total of 20 journals published between 2019 and 2024 were reviewed, sourced from Google Scholar. The objective of this literature review is to gather information and data based on parameters determined by the researchers. The findings indicate that the utilization of blockchain for data security in the healthcare sector is predominantly applied to Electronic Medical Records (EMR). Furthermore, despite blockchain's significant potential across various fields, particularly in healthcare, this literature review also highlights several limitations of blockchain technology. The conclusion of this study suggests that with further innovation, blockchain can play a crucial role in enhancing security within digital healthcare, making it safer and more efficient.